Directions of development and application of plasma nitriding in industry - Željko Stojanović; Sanja Stanisavljev; Spasoje Erić (Zaštita Materijala)
This paper presents a discussion of the results of previous research of the effects of surface modification of structural materials and tool steels using plasma nitriding (PN) in order to improve their mechanical, tribological and corrosion behavior. The paper discusses the current status and future directions in the application of PN on various wearing components that are exposed to high loads, stresses and frequent temperature changes. The paper provides an overview of the relevant literature whose results show the most favorable or optimal parameters of the PN process aimed at achieving the best performance in terms of wear and corrosion resistance and hardness increase for the various materials considered. Systematization of literature data about research of the impact of low-temperature PN on stainless steels has placed emphasis on those process mechanisms that achieve benefits for surface layers without creating negative side effects in the form of loss of corrosion resistance. The strengthening of hot forging dies is considered through the reasons and problems that cause the need for the application of PN, and then paper focuses on the role of PN in achieving the tribological properties required to extend the service life of the die. Publications in which the nitriding of titanium alloys is investigated through the reduction of wear, increase of bearing capacity and microhardness depending on the input parameters of the process, ie the optimal parameters applied in order to obtain the best performance characteristics are cited. The application of PN to aluminum and its alloys is discussed, as well as the conditions of testing and the achieved improvements.